Answer:
[tex]x=-\frac{3}{2}, x=\frac{3}{2}[/tex]
Step-by-step explanation:
(1) To solve by factoring,
Given equation: [tex]4 x^{2}=9[/tex]
Subtract 9 from both sides of the equation.
[tex]\begin{aligned}&4 x^{2}-9=9-9\\&4 x^{2}-9=0\\&(2 x)^{2}-3^{2}=0\\&(2 x-3)(2 x+3)=0\end{aligned}[/tex]
Using zero factor principle, [tex]2 x-3=0,2 x+3=0[/tex]
The solutions are [tex]x=-\frac{3}{2}, x=\frac{3}{2}[/tex].
(2) To solve by complete the square ,
Given [tex]4 x^{2}=9[/tex]
Divide both sides of the equation by 4.
[tex]\frac{4 x^{2}}{4}=\frac{9}{4}[/tex]
[tex]\Rightarrow x^{2}=\frac{9}{4}[/tex]
Square root on both sides.
[tex]$\Rightarrow x=\pm \frac{3}{2}$[/tex]
[tex]x=-\frac{3}{2}, x=\frac{3}{2}[/tex]
(3) To solve by quadratic formula,
[tex]$4 x^{2}-9=0$[/tex]
Here, a = 4, b = 0, c = –9
Quadratic formula, [tex]$x=\frac{-b \pm \sqrt{b^{2}-4 a c}}{2 a}$[/tex]
[tex]x=\frac{-0 \pm \sqrt{0^{2}-4 \times 4 \times(-9)}}{2 \times 4}[/tex]
[tex]\begin{aligned}&\Rightarrow x=\frac{\pm \sqrt{144}}{8}\\&\Rightarrow x=\pm \frac{3}{2}\\&\Rightarrow x=\frac{3}{2}, x=-\frac{3}{2}\end{aligned}[/tex]